An Interview with Hermann Kant - Joan E. Holmes (Studies in 20th & 21st Century Literature, 1979)
In an interview with Joan E. Holmes (University of Kansas), Hermann Kant, novelist and current president of the Writers Union of the German Democratic Republic (GDR or East Germany), discusses his own work, literary developments since 1949 in the GDR, and the changing concept of socialist realism. Central to all of these topics is the role of the writer and the function of literature in a socialist system, a question which resulted in a heated controversy during the summer and fall of 1979 in the GDR. The crux of the matter lies in the nature of Marxist theory and is at least as old as the Sickingen debate of 1859, when Marx, Engels and Lassalle discussed the kind of literature that the fledgling socialist movement should encourage in order to promote the building of a future communist society. The question of the role of the author and the function of literature has reappeared since that time in various forms—in the formulation of the concept of socialist realism in the 1930's by Gorki and Soviet Party Secretary Zhadanov, in the formalism debates of the 1950's, in the dictates of the Bitterfelder Way (1960's), and in the liberalizing influence of the proclamations of the Eighth Party Congress in 1971. Since the Ninth Party Congress (May 1976), the controversy has become a critical matter in the cultural policies of the GDR, a country where literature is considered an important political tool. Hermann Kant, in the tradition of the Eighth and Ninth Party Congresses, presents in this interview a broad interpretation of the concept of socialist realism, while at the same time strongly emphasizing the responsibility of the author vis à vis the socialist society. He questions whether too much rapid change can be beneficial for East Germany, and suggests that both tolerance and caution are required.
Keywords: Hermann Kant; University of Kansas; Writers Union of the German Democratic Republic; DDR; GDR; East Germany; socialist realism; Marxist theory; marxism; role of the author; Bitterfelder Way; Ninth Party Congress; socialist society